Formulation and Evaluation of Topical Gel Containing Nepalese Medicinal Plants - Gyawal, Rajendra; Aryal, Sadhana; Upreti, Bishal; Bhatta, Yub Raj; Yadav, Manish Kumar; Singh, Debendra; Shrestha, Joshna (Journal of Karnali Academy of Health Sciences, 2022)
Background: The formulation of herbal gel offers a great advantage in non-sticky products as compared to ointmentsand creams. Herbs are beneficial for human health containing several phytochemicals. Traditionally herbal preparationsare used to enhance and facilitate the quality of the skin. Therefore, the aim of the present study was to prepare the herbalgel for the use of skin nourishing and help to cure skin related disease.Methods: Different crude drugs like Aloe (Aloe vera), Neem (Azadiracta indica), Turmeric (Curcuma longa),Onion(Allium cepa), and Basil (Ocimum tenuiflorum) are used to formulate the gel. Selection of these herbs are based onliterature review on their individual uses in skin related problems. Formulation was developed from polymer base byexperimental design based on previous works. Different compositions of herbs were designed for the formulation study.The water extract of the herb was prepared individually and later on mixed with the gel base ingredients containingcarbopol 934, methylparaben and propyl paraben. The gel is subjected to evaluation of organoleptic properties andconsistency, pH, and spreadability. Disk diffusion method was used to evaluate the antimicrobial property of the extract.DPPH method was used to determine the antioxidant property of extracts.Results: The average pH values of the formulations were 6.12 and 5.91, similarly spreadability of the two formulationsF and S were 9.223 and 9.336 respectively. All the parameters were within the range. The antimicrobial study showedthat both of the formulations have strong antimicrobial property to E.coli.Conclusion: The study concludes that the developed formulation of different concentrations are safe and within the rangeof standard. Therefore, we can say that our formulation product is one of the good natural gels which can be consideredfor the antioxidant benefit.